ETHNOLOGICAL ANALYSIS OF UZBEK GIRLS-REARING PRACTICES IN POST-SOVIET UZBEKISTAN - Bahridil Ergasheva (Western European Studies, 2025)
This article analyzes the issue of raising girls in Uzbek families during the Soviet era from a historical and anthropological perspective. The study sheds light on the changes in family values, the reshaping of gender roles, and the impact of socio-spiritual factors on the upbringing of girls on a scientific basis. Based on archival documents, period literature, statistical data, and modern ethnographic observations, the transformations that occurred in the upbringing of girls as a result of Soviet policy are revealed. The relationship between national traditions and new sociocultural trends introduced by the state is also scientifically discussed. The results of the article serve to deepen our understanding of the complex dynamics of raising girls in Uzbek society between nationality and modernity
Keywords: raising girls; Soviet era; family